Faktor-faktor yang mempengaruhi kualitas hidup pasien diabetes mellitus dengan Ulkus diabetikum - Utami, Desni Tri; Karim, Darwin -; -, Agrina - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to determined the factors that affect quality of life diabetes mellitus patient with diabetic ulcers. The design was descriptive correlational design with cross sectional approach. The sampling technique was consecutive sampling with 30 respondents which was selected based on inclusion criteria. This research used instrument a questionnaire. This research used univariate and bivariate analysis with chi-square test. The results showed a correlation between age, complications experienced (other diseases), and anxiety quality of life of patients with diabetes mellitus with diabetic ulcers (p value 0,011; 0,046 and 0,030) and no correlation between marital status and duration of diseases (p value 0,440 and 0,399). The research recommends diabetic patients with diabetic ulcers to maintain the state of her health condition and keep doing treatment as well as to control the activity, and the diet so the disease get worse so and their quality of life will be better. Keyword: Diabetes Mellitus, diabetic ulcers , quality of life